Are courts representative bodies? A canadian perspective - Sharpe, R (2012)
In this policy brief, Judge Robert Sharpe of the Court of Appeal for Ontario argues that it would be wrong for judges exercising the power of judicial review to claim legitimacy as representatives. He argues that the claim is not only wrong, it is dangerous as it distorts the nature of the judicial function. Judicial review of legislation against constitutionally mandated standards can only be defended for what it is: independent judges acting as impartial adjudicators applying legal method and argument. If judges deceive themselves into thinking they are representative and fail consciously to relatethe exercise of the power of judicial review to their non-representational role, they are likely to exceed acceptable limits of judicial authority. The legitimacy of judicial review rests on the perception that courts are not representative of anybody or anything other than the law and act as independent and impartial arbiters who base their decisions on legal argument and reasoning rather than on political judgment.